The Model of Development of Flexibility Competence of Education Teachers in the System of Professional Development - Sayyora Toraeva (International Journal on Integrated Education, 2022)
The article describes the issue of developing the competence of flexibility of education teachers in the system of professional development. The general characteristics and detailed description of the educational model for the development of flexibility competences in pedagogical activity of teachers of education are described. The conceptual basis of the model is determined, the principles of education are distinguished, the construction technology of the educational process directed at the development of the teacher's flexibility competencies in pedagogical activities is described.